Impact of Weather Shocks on MENA Households - Wodon, Quentin; Liverani, Andrea (World Bank, Washington, DC, 2015)
Do households living in climate affected areas in the MENA region believe that changes in climate patterns and their environment are taking place? Have households been affected by extreme weather events, and if so to what extent and which events have had the largest impact? What are the coping strategies that households declare having used, or could be using to cope with climate change and weather shocks? And what are the implications for policy? A new World Bank Study by Wodon et al. (2014) helps in answering these questions. It is widely recognized that MENA will be strongly affected by climate change. The frequency and severity of extreme weather shocks is expected to increase. Yet, the evidence on how households are already affected and whether they can cope and adapt to changing climatic conditions is limited. The study by Wodon et al. (2014) helps fill these knowledge gaps. It is based in large part on new household surveys and qualitative data from climate affected areas in Algeria, Egypt, Morocco, Syria, and Yemen. The study provides insights on household perceptions of, and vulnerability to, extreme weather shocks.